2018
DOI: 10.1002/adfm.201707568
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Induced Surface Modification of Natural Plant Microparticles: Toward Colloidal Science and Cellular Adhesion Applications

Abstract: Playing an instrumental role in the life of plants, pollen microparticles are one of the most fascinating biological materials in existence, with abundant and renewable supply, ultrahigh durability, and unique, species-specific architectural features. Aside from their biological role, pollen microparticles also demonstrate broad utility as functional materials for drug delivery and microencapsulation, and increasingly for emulsion-type applications. As natural pollen microparticles are predominantly hydrophobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…TENGs based on natural materials have been recently investigated in detail, and the conclusions showed that their complex surface architecture causes major impacts on the produced charge, current, or voltage [48][49][50][51]. Since natural materials have hierarchically structured surfaces, surface modification is not required in many cases, and they can be used for polymer modification by soft lithography as well [52][53][54]. Besides, the combination of natural materials with biocompatible polymers allows the production of eco-friendly triboelectric pairs for energy harvesting.…”
Section: Natural Materialsmentioning
confidence: 99%
“…TENGs based on natural materials have been recently investigated in detail, and the conclusions showed that their complex surface architecture causes major impacts on the produced charge, current, or voltage [48][49][50][51]. Since natural materials have hierarchically structured surfaces, surface modification is not required in many cases, and they can be used for polymer modification by soft lithography as well [52][53][54]. Besides, the combination of natural materials with biocompatible polymers allows the production of eco-friendly triboelectric pairs for energy harvesting.…”
Section: Natural Materialsmentioning
confidence: 99%
“…important to note that upon more detailed analysis of the narrow scan XPS data, the increase in COR binding can be attributed to ether (COC) binding rather than COH binding ( Table 5.1). attributed to UV-O induced aromatic ring opening [25]. Importantly, the oxidative degradation of the aromatic compound p-coumaric acid has been shown to produce ketone (R2C=O) moieties [24], and p-coumaric acid is known to be one of the major constituents of sporopollenin [22].…”
Section: Discussionmentioning
confidence: 99%
“…The earliest chemical structure for sporopollenin was proposed in the 1930s that terpenoids which is a class of naturally occurring that is similar to terpenes that are produced by plants to ward off herbivores [18]. And in the 1960s sporopollenin was proposed to be composed of carotenoids or are lipidic in as the cinnamic acids, p-coumaric acid and ferulic acid [21][22][23][24][25][26][27]. These studies were mostly done with sporopollenin extracted from lycopodium, pine and cattail.…”
Section: Sporopollenin As Key Materials Of Pollenmentioning
confidence: 99%
See 2 more Smart Citations